2017
DOI: 10.3171/2017.10.focus17472
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of frailty as a tool for risk stratification in adult spinal deformity surgery

Abstract: OBJECTIVEThe goal of this study was to analyze the value of an adult spinal deformity frailty index (ASD-FI) in preoperative risk stratification. Preoperative risk assessment is imperative before procedures known to have high complication rates, such as ASD surgery. Frailty has been associated with risk of complications in trauma surgery, and preoperative frailty assessments could improve the accuracy of risk stratification by providing a comprehensive analysis of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
157
1
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(166 citation statements)
references
References 20 publications
4
157
1
4
Order By: Relevance
“…Radiographic pelvic tilt in the sagittal plane is considered to be a crucial compensatory mechanism for subjects with sagittal malalignment and the maximal amount of pelvic tilt that a subject can perform is known to be limited by his maximal capacity of hip extension [15]. Moreover, rPT is an essential parameter that is used in different classifications of adult spinal deformity patients [24][25][26][27][28][29]44] and is known to be increased in this specific population whose quality of life is affected [15]. Thus, when the hip extension reserve is used, mobility of the pelvis might be limited.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiographic pelvic tilt in the sagittal plane is considered to be a crucial compensatory mechanism for subjects with sagittal malalignment and the maximal amount of pelvic tilt that a subject can perform is known to be limited by his maximal capacity of hip extension [15]. Moreover, rPT is an essential parameter that is used in different classifications of adult spinal deformity patients [24][25][26][27][28][29]44] and is known to be increased in this specific population whose quality of life is affected [15]. Thus, when the hip extension reserve is used, mobility of the pelvis might be limited.…”
Section: Resultsmentioning
confidence: 99%
“…Subjects were enrolled in the study if their age was above 18 years and had no history of orthopedic surgery to either the spine, pelvis or lower limbs. The exclusion criteria were pain, including lower back pain at the time of the study or any musculoskeletal disease (scoliosis, Scheuermann's kyphosis or leg length discrepancies) or the presence of at least one radiological criteria of adult spinal deformity (based on the European and International Spine Study Groups [24][25][26][27][28][29]) or previous orthopedic surgeries. A written informed consent form was signed by each subject.…”
Section: Methodsmentioning
confidence: 99%
“…40 In an adult spinal deformity population, Miller and colleagues noted increased risk of junctional kyphosis (odds ratio [OR] 2.8), pseudarthrosis (OR 13.0), deep wound infection (OR 8.0), and wound dehiscence (OR 13.4) as compared with non-frail patients. 41 A recent systematic review of the literature found that despite discrepancies in measurement tools, frailty is a consistent predictor of mortality, minor and major morbidity, in-hospital LOS, and discharge disposition in patients undergoing spine surgery. 42 Traditionally, however, frailty is a concept that has been intimately linked with older age.…”
Section: Discussionmentioning
confidence: 99%
“…The leading frailty indices in the spine literature are as follows: mFI; Adult Spinal Deformity Frailty Index (ASD-FI); and the Cervical Deformity Frailty Index (CD-FI). [32][33][34][35] Although both the frailty index model and frailty phenotype measures have pros and cons, some have concluded that the frailty index model remains the most versatile with wide applicability for both research and clinical use, as it quantifies the concept of frailty. 36,37 Moskven et al 38 identified mFI as the most viable current option for assessing, quantifying, and stratifying the severity of frailty in patients undergoing spine surgery.…”
Section: Discussionmentioning
confidence: 99%